2016
DOI: 10.1080/00405000.2016.1193982
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mechanical behavior of composites made from textile industry waste

Abstract: Recycling the waste for environmental protection has been an important challenge for the mankind. The fibrous waste in textile industry accounts for approximately 15% of the amount of fibers used, leading to a lower yield %. The current study focused to use this waste as reinforcement to produce a fiber-reinforced polymer composites. Reinforcements were woven in 3/1 S twill, using yarn produced from noil waste and knitting waste in the weft direction. The weft yarn count, type of waste material and number of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 17 publications
(16 reference statements)
0
29
0
Order By: Relevance
“…There are four prime ways of reusing discarded or waste textiles as a reinforcement for composite manufacturing. The reinforcement could be waste fabric, [ 19 ] fibers extracted by shredding the waste textiles, [ 20 ] yarns, woven or nonwoven fabric [ 21 ] obtained by reorganizing the extracted waste fibers, and nano or microstructures developed from waste textiles. [ 6 ] Multiple studies detailed textile waste‐reinforced composites as a replacement of wood or wood particle boards.…”
Section: Introductionmentioning
confidence: 99%
“…There are four prime ways of reusing discarded or waste textiles as a reinforcement for composite manufacturing. The reinforcement could be waste fabric, [ 19 ] fibers extracted by shredding the waste textiles, [ 20 ] yarns, woven or nonwoven fabric [ 21 ] obtained by reorganizing the extracted waste fibers, and nano or microstructures developed from waste textiles. [ 6 ] Multiple studies detailed textile waste‐reinforced composites as a replacement of wood or wood particle boards.…”
Section: Introductionmentioning
confidence: 99%
“…3 The waste textiles can be successfully employed to develop composite boards for applications like furniture materials, subflooring, roofing materials, support for outdoor signs, automotive components and so on. [4][5][6] Umar et al 7 reported two different types of woven fabrics as reinforcement for thermoset composites. The reinforcement materials consist of cotton yarn, used as warp, and the yarn produced from comber noil and knitting waste, used as weft.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, used fabrics could be utilized again through polymeric matrix reinforcement, which may impart significant mechanical properties by having extensive potentiality in terms of sustainable products through minimizing carbon footprints. Umar et al [177] conducted a study on waste materials from a textile industry having both types of knit and woven wastes fabricated into laminated composites. The developed composites provided significant mechanical features that are compatible with glass fiber-reinforced composites [177].…”
Section: Environmental Influence Of Fabrics-based Compositesmentioning
confidence: 99%
“…Umar et al [177] conducted a study on waste materials from a textile industry having both types of knit and woven wastes fabricated into laminated composites. The developed composites provided significant mechanical features that are compatible with glass fiber-reinforced composites [177]. Chen et al conducted a study on recycled silk fabrics produced from silk waste and reinforced with epoxy poly(butylene) succinate (PBS) and found superior performance characteristics [178].…”
Section: Environmental Influence Of Fabrics-based Compositesmentioning
confidence: 99%